SOCIAL EXCLUSION AS REPRESENTATION LEGITIMATOR OF INSTITUTIONAL VIOLENCE IN JESUS DE NAZARETH - LUCAS GUIMARÃES, Ariane (2021)
It intends to analyze introductory the concept of social exclusion as a synthesis of the construction of the imaginary about the urban periphery of Vitória-ES, more specifically the neighborhood Jesus de Nazareth. The idea of discourse as an instrument of power and justification for institutional violence was used as a framework for social representation in the analysis of reports about the place. These were selected from alocal newspaper portal, where the name of the neighborhood appeared. In the results found in the survey, we separated into large categories, for analysis of cases of violence reported in the neighborhood. More than half of the news are on the themes: public works/maintenance, police actions/crime, cultural programs and actions by the local community/tourism. However, police action/criminality has little expression, sincemore than half of the news reports report the same phenomena. These are two major police operations in the area where human and logistical investment in both were not consistent with the apprehensions. We understand that the stigma of poverty in the formation of social exclusion in urban peripheries tends to intensify in the recognition of symbolic language, that is, in the elaboration and recognition of discourses.